Restoration of damaged ecosystems in desert steppe open‐pit coal mines: Effects on soil nematode communities and functions. (12th August 2021) - Han, Chaowei; Gao, Zhiwei; Wu, Zhaohui; Huang, Jing; Liu, Ziying; Zhang, Li; Zhang, Guogang
Abstract: Repair of damaged areas in open‐pit (opencast) coal mines has emerged as an important environmental concern. Our research investigated the mechanism by which different ecological restoration methods affected soil nematode communities in damaged areas of desert steppe coal mines. Using high‐throughput sequencing technology, nematode community composition, diversity, and function were analyzed to determine the response of nematodes to different ecological restoration methods in damaged areas of coal mines. For slope rehabilitation, vegetation blanket restoration exhibited more favorable effects than those exhibited by vegetation bag restoration and natural restoration. For rehabilitation of the platform area under the slope, the diversity of soil nematodes and the soil fauna analysis under alien soil restoration conditions were performed and exhibited similar characteristics to those of the native vegetation. Findings based on Linear discriminant analysis Effect Size (LEfSe) multi‐level discriminant analysis and determination of shared genera suggest that Paraphelenchus, Cervidellus, Panagrolaimus, Microdorylaimus, Cephalobus, and Ecumenicus may be the key genera of soil nematodes in the damaged ecosystem of open‐pit coal mines in the desert steppe. We found that reasonable water and fertilizer management in slope restoration and under‐slope platform area restoration may play a key role in the restoration of damaged ecosystems in open‐pit coal mines. We comprehensively analyzed the response of soil nematode communities and their functions to different ecological restoration methods, and provided a reference for evaluating the quality of underground ecosystem restoration of damaged areas in abandoned desert steppe open‐pit coal mines.